2014
DOI: 10.4049/jimmunol.1302783
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution and Dependence of Responsiveness of Human Antigen-Specific Memory B Cells

Abstract: Memory B cells (mBCs) are a key to immunologic memory, yet their distribution within lymphoid organs and the individual role of these for mBC functionality remain largely unknown. This study characterized the distribution and phenotype of human (Ag-specific) mBCs in peripheral blood (PB), spleen, tonsil, and bone marrow. We found that the spleen harbors most mBCs, followed by tonsils, BM, and PB, and we detected no major differences in expression of markers associated with higher maturity. Testing the distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 63 publications
9
62
0
Order By: Relevance
“…4). While this may be considered a low frequency, the median of 0.7% for this group is nonetheless approximately 10-fold higher than frequencies of tetanus toxoid-specific PCs reported following immunization with tetanus toxoid (31). Of note, the approach taken to measure the Env-specific ASC frequencies does not provide information on Env-specificity per Ig isotype and obtaining such information would be technically difficult and require twice or more the number of cells used in the current assay.…”
Section: Resultsmentioning
confidence: 58%
“…4). While this may be considered a low frequency, the median of 0.7% for this group is nonetheless approximately 10-fold higher than frequencies of tetanus toxoid-specific PCs reported following immunization with tetanus toxoid (31). Of note, the approach taken to measure the Env-specific ASC frequencies does not provide information on Env-specificity per Ig isotype and obtaining such information would be technically difficult and require twice or more the number of cells used in the current assay.…”
Section: Resultsmentioning
confidence: 58%
“…CD27Ϫ memory B cells have been reported to reside within the tonsil and possibly other secondary lymphoid organs (21,42). Their appear-ance in the circulation of SLE patients may therefore reflect the generalized B cell overactivity that is characteristic of SLE, with overflow of this population into the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Memory B lymphocytes of the bone marrow have not been analyzed extensively 181, 182. Paramithiotis and Cooper showed a preferential localization of IgM and IgD expressing CD24 low CD10 − B lymphocytes with somatically mutated antibody genes indicative of antigen experience in the bone marrow 182.…”
Section: Memory B Lymphocytes Of the Bone Marrowmentioning
confidence: 99%
“…Tetanus‐specific memory B cells were present in all organs analyzed. They concluded that switched memory B lymphocytes of all organs were part of one, circulating population of memory B lymphocytes 181. However, a comprehensive repertoire analysis of memory B lymphocytes of various organs, with the aim to identify resident memory lymphocytes, has not been performed yet.…”
Section: Memory B Lymphocytes Of the Bone Marrowmentioning
confidence: 99%